2022
DOI: 10.1093/mnras/stac532
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency wideband timing of InPTA pulsars observed with the uGMRT

Abstract: High-precision measurements of the pulsar dispersion measure (DM) are possible using telescopes with low-frequency wideband receivers. We present an initial study of the application of the wideband timing technique, which can simultaneously measure the pulsar times of arrival (ToAs) and DMs, for a set of five pulsars observed with the upgraded Giant Metrewave Radio Telescope (uGMRT) as part of the Indian Pulsar Timing Array (InPTA) campaign. We have used the observations with the 300 – 500 MHz band of the uGMR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…We have scaled the ToA uncertainties by a factor of bandwidth 100 MHz duration 30 min ( ) ´(following scaling similar to that of Nobleson et al 2022;Alam et al 2021b) to compare the ToA precision obtained in our work with the values from other highprecision timing studies. We have also scaled the raw ToA uncertainties reported in Krishnakumar et al (2021).…”
Section: Comparison With Other High-precision Timing Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…We have scaled the ToA uncertainties by a factor of bandwidth 100 MHz duration 30 min ( ) ´(following scaling similar to that of Nobleson et al 2022;Alam et al 2021b) to compare the ToA precision obtained in our work with the values from other highprecision timing studies. We have also scaled the raw ToA uncertainties reported in Krishnakumar et al (2021).…”
Section: Comparison With Other High-precision Timing Studiesmentioning
confidence: 99%
“…We have also scaled the raw ToA uncertainties reported in Krishnakumar et al (2021). Table 6 shows a comparison of scaled ToA and raw DM precision obtained from Krishnakumar et al (2021;InPTA), Nobleson et al (2022;InPTA), Alam et al (2021b;NANOGrav), and this work. Krishnakumar et al (2021) reported ToA and DM precision for five PTA pulsars, including J1713+0747, J1909−3744, and J2145−0750, from simultaneous 400-500 MHz (with five antennas of the uGMRT array) and 1360-1460 MHz (with 12 antennas of the uGMRT array) observations using the multiple-subarray mode of the uGMRT.…”
Section: Comparison With Other High-precision Timing Studiesmentioning
confidence: 99%
See 3 more Smart Citations